Central Bank Vulnerability and the Credibility of Commitments : A Value-at-Risk Approach to Currency Crises - Schumacher, Liliana; Blejer, Mario (Washington, D.C. : International Monetary Fund, 1998)
A loss of solvency increases central bank vulnerability, reducing the credibility of commitments to defend a nominal regime, including an exchange rate peg. This paper develops a methodology to assess central bank solvency and exposure to risk. The measure, based on Value-at-Risk, is frequently used to evaluate commercial risk. The paper emphasizes that the ability to sustain nominal commitments cannot be gauged by focusing only on selected accounts (such as reserves), but requires a comprehensive solvency and vulnerability analysis of the monetary authorities' complete portfolio (including off-balance-sheet operations). The suggested measure has powerful reporting value and its disclosure could improve monitoring of sovereign solvency risk.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet